Imam al-Shafi‘i’s Fiqh on Women as Rukyatul Hilal Witnesses: A Hermeneutic and Maslahah Perspective - Nazilah salsabila; Ahmad Izzuddin; Eman Sulaeman; Muhammad David Ibrahim; Ahmad Aniq Ulin Naim; Muhammad Maulana Iqbal (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2025)
The exclusion of women from witnessing rukyat al-hilal remains a critical issue in contemporary Islamic jurisprudence, raising questions about gender inclusivity and the contextual interpretation of classical fiqh. This research reexamines Imam al-Shafi‘i’s fiqh concerning the prohibition of women serving as witnesses in rukyat al-hilal. The prohibition originally arose within a classical social context where women had limited access to astronomy. However, in the modern era, many women have acquired advanced expertise in astronomy and actively participate in determining the beginning of the lunar month. Therefore, this prohibition has lost its relevance and may contribute to the subordination of women in religious decision-making. Using a hermeneutic approach and Najmuddin al-Tufi’s theory of maṣlaḥah mursalah, the study finds that Imam al-Shafi‘i formulated his legal opinions by considering the social conditions of his time, as reflected in his qaul qadim and qaul jadid. Theoretically, this study highlights that fiqh is dynamic and responsive to changing contexts. Practically, it suggests that accepting the testimony of competent women in rukyat al-hilal aligns with the maqāṣid al-sharī‘ah in developing a more inclusive and adaptive Islamic legal system.